2012
DOI: 10.1016/j.expneurol.2011.12.034
|View full text |Cite
|
Sign up to set email alerts
|

The NMDA-NR1 receptor subunit and the mu-opioid receptor are expressed in somatodendritic compartments of central nucleus of the amygdala neurons projecting to the bed nucleus of the stria terminalis

Abstract: The pathway between the central nucleus of the amygdala (CeA) and the bed nucleus of the stria terminalis (BNST) is emerging as a critical mediator of stress-related affective processes. Evidence also indicates that exposure to drugs of abuse, like opioids, is associated with NMDA-type glutamate receptor-dependent plasticity in the CeA and BNST. However, there is little evidence that NMDA receptors are expressed in CeA neurons projecting to the BNST, or are required for opioid-induced BNST neural activation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 65 publications
(107 reference statements)
4
23
0
Order By: Relevance
“…In the present study, the general pattern of CRF, as well retrograde labeling, in the mouse was found to be in agreement with prior studies in this species (Beckerman and Glass 2012; Treweek et al 2009), and in the rat as well (Cassell and Gray 1989; Jaferi and Pickel 2009; Justice et al 2008; Treweek et al 2009). These broad anatomical similarities correspond to generally similar responses of the CeA CRF system to relevant behaviors, including exposure to, or withdrawal from, drugs of abuse (McNally and Akil 2002; Nie et al 2004; Roberto et al 2010; Shaw-Lutchman et al 2002), in addition to conditioned fear behaviors (Kolber et al 2008; Thompson et al 2004).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the general pattern of CRF, as well retrograde labeling, in the mouse was found to be in agreement with prior studies in this species (Beckerman and Glass 2012; Treweek et al 2009), and in the rat as well (Cassell and Gray 1989; Jaferi and Pickel 2009; Justice et al 2008; Treweek et al 2009). These broad anatomical similarities correspond to generally similar responses of the CeA CRF system to relevant behaviors, including exposure to, or withdrawal from, drugs of abuse (McNally and Akil 2002; Nie et al 2004; Roberto et al 2010; Shaw-Lutchman et al 2002), in addition to conditioned fear behaviors (Kolber et al 2008; Thompson et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Somata of CeA neurons expressing labeling for FG and CRF contained large nuclei and a dense endomembrane system, both cytological features similar to CeA-BNST projection neurons that express NR1 and mu-opioid receptor as previously shown by triple labeling immunocytochemistry (Beckerman and Glass 2012). In addition to co-expression in somata and dendrites, both single FG labeled, and dual FG and CRF labeled somata and dendrites were contacted by CRF expressing axon terminals.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Reduced labeling for this antiserum has been shown following rAAV-Cre administration into the brain of floxed GluN1 mice [55, 56]. Specificity of the GluN1 antibody was characterized via immunoprecipitation and immunohistochemistry [57–59].…”
Section: Methodsmentioning
confidence: 99%